A case report of idiopathic environmental intolerance: A controversial and current issue. Issue 1 (26th November 2019) - Quarato, Marco; De Maria, Luigi; Caputi, Antonio; Cavone, Domenica; Cannone, Enza Sabrina Silvana; Mansi, Francesca; Gatti, Maria Franca; Vimercati, Luigi
Abstract: In this case of idiopathic environmental intolerance, a little known disease characterized by many symptoms of irritation due to exposure to several toxic compounds, genetic analysis could be helpful in case of differential diagnosis issue. Abstract : In this case of idiopathic environmental intolerance, a little known disease characterized by many symptoms of irritation due to exposure to several toxic compounds, genetic analysis could be helpful in case of differential diagnosis issue.